2006
DOI: 10.1097/01.ajp.0000208246.18251.f2
|View full text |Cite
|
Sign up to set email alerts
|

Women Suffer More Short and Long-term Pain Than Men After Major Thoracotomy

Abstract: Women have a distinctly different pain experience than men after thoracic surgery and probably require novel and/or multimodal analgesic regimens to improve their comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
4
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 35 publications
6
44
4
4
Order By: Relevance
“…A média de idade também se mostrou semelhante (40 anos versus 46 (2) ). Os dados do atual estudo indicam que a busca por serviços de saúde e a maior atenção à saúde ocorrem com maior frequência em pacientes do sexo feminino, fato também reportado na literatura (24) . Houve relação significativa entre o sexo e o diagnóstico/tipo de cirurgia (p<0,01) no presente estudo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A média de idade também se mostrou semelhante (40 anos versus 46 (2) ). Os dados do atual estudo indicam que a busca por serviços de saúde e a maior atenção à saúde ocorrem com maior frequência em pacientes do sexo feminino, fato também reportado na literatura (24) . Houve relação significativa entre o sexo e o diagnóstico/tipo de cirurgia (p<0,01) no presente estudo.…”
Section: Discussionunclassified
“…Esse fator pode apresentar significativa influência na intensidade da DPO (2,24,25) . Em hospitais generalistas, a cirurgia geral é a mais comum entre as especialidades cirúrgicas realizadas, seguida pelas ginecológica, proctológica, vascular e mastológica (2) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There is no clear evidence to suggest sex predominance but it was observed that women tended to report higher levels of pain with concomitant use of simple analgesics. And younger patients reported more pain as compared to the elderly 19 . There is little consensus regarding the impact that the type of surgery has on the clinical outcome in terms of PTPS.…”
Section: Epidemiologymentioning
confidence: 94%
“…24,25,27,28 There is evidence to suggest a gender difference where women may be at a higher risk of developing post surgical pain. 19,28 Currently there is no definitive evidence to suggest that post thoracotomy pain has age or gender preponderance.…”
Section: Demographic Factorsmentioning
confidence: 99%